Sign Language-Based Visualization of Science Terminology: A Science Literacy Solution for Deaf Students - Made Mahaputra; Putu Nanci Riastini; I Wayan Ardana (Jurnal Ilmiah Sekolah Dasar, 2026)
This research is driven by the significant barriers deaf students face in understanding abstract science terminology and the lack of sign language-based learning resources. The primary objective of this study is to design the interface, analyze the level of content validity, and analyze user responses to the SIBIPA website as a translation tool for Grade IV Science terminology. The research method employed is Research and Development (R&D) using the ADDIE model development design. Research subjects involved two content experts, two media experts, three educational practitioners, and nine deaf students. Data were collected via validation sheets and questionnaires, then analyzed using the Gregory technique and descriptive percentage statistics. Results indicate that the SIBIPA website possesses very high content validity, achieving a Gregory coefficient of 1.00. Practicality levels based on teacher responses reached 95.8% and student responses reached 96.3%, both categorized as very practical. The implication of these findings is the provision of adaptive visual information accessibility to support science literacy for deaf students in inclusive environments. In conclusion, the SIBIPA website is a valid and highly practical learning resource innovation for facilitating the understanding of science concepts in elementary education.